2007
DOI: 10.1007/s10570-007-9145-9
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of cellulose and preparation of nanocellulose from sisal fibers

Abstract: In this work a study on the feasibility of extracting cellulose from sisal fiber, by means of two different procedures was carried out. These processes included usual chemical procedures such as acid hydrolysis, chlorination, alkaline extraction, and bleaching. The final products were characterized by means of Thermogravimetric Analysis (TGA), Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD), Differential Scanning Calorimetry (DSC) and Scanning Electronic Microscopy (SEM). The extraction procedures that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
583
3
21

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,269 publications
(727 citation statements)
references
References 21 publications
42
583
3
21
Order By: Relevance
“…RHB demonstrated a less intense peak at the identical temperature and the raw material (RH) demonstrated an endothermic peak at 328°C (Figure 6). Morán et al, 39 reported that commercial cellulose contained endothermic peaks related to its crystal melting at 330°C and that a decrease in the position of the peak indicates an increase in the amount of amorphous cellulose. We report similar results for RHB, RHNF1 h and RHNF2 h (higher crystallinity index) compared to RH.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
“…RHB demonstrated a less intense peak at the identical temperature and the raw material (RH) demonstrated an endothermic peak at 328°C (Figure 6). Morán et al, 39 reported that commercial cellulose contained endothermic peaks related to its crystal melting at 330°C and that a decrease in the position of the peak indicates an increase in the amount of amorphous cellulose. We report similar results for RHB, RHNF1 h and RHNF2 h (higher crystallinity index) compared to RH.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
“…Atšķirībā no celulozes, hemiceluloze ir amorfs biopolimērs, kas sastāv no dažādiem cukuriem, tādiem kā ksiloze, mannoze un glikoze. [20] Cukuru sastāvs hemicelulozē mainās atkarībā no auga šķirnes, augšanas un klimatiskiem apstākļiem, vietas augā u.c.…”
Section: šķIedru Morfoloģiskais Raksturojumsunclassified
“…There is also a possibility that there are impurities such as hemicellulose in the sample. The peaks at wavelength number of 3337-3331 cm -1 and 2918-2890 cm -1 , which existed in all spectra referred to the free-OH and stretch C-H group on the sample, respectively [4].…”
Section: Extraction Yieldsmentioning
confidence: 92%
“…However, the nypa fruit husk is usually disposed. Nypa fruit husk has been reported to be consisted of 37 % cellulose, 22 % hemicellulose and 29 % lignin [4]. Therefore, the potential of nypa fruit husk as the primary source for producing cellulose is very promising while value added to the agriculture waste.…”
Section: Introductionmentioning
confidence: 99%